Dissociative Aphonia Secondary to Nonorganic Vaginismus—A Case Report - Nikita Prasanna Nalawade; Suma T. Udupa; Samir Kumar Praharaj (Journal of Psychosexual Health)
Dissociative aphonia is a rare disorder with a point prevalence of 0.4%, while psychogenic vaginismus occurs at a prevalence of about 1–7%. The etiology roots down to underlying factors including dysfunctional sexual beliefs, fear of pain as well as other psychosocial conflicts. We report a 26-year-old married lady who presented with sudden onset aphonia in the background of nonorganic vaginismus. There were covert conflicts which seemed to stem from her early childhood and home atmosphere, the eventual spillover of this into her adulthood, precipitated her symptoms. This emphasizes the need for a broader outlook on the management of the disorder beyond the symptomatic treatment.